2015
DOI: 10.1186/s12943-015-0384-3
|View full text |Cite
|
Sign up to set email alerts
|

Human anti-CAIX antibodies mediate immune cell inhibition of renal cell carcinoma in vitro and in a humanized mouse model in vivo

Abstract: BackgroundCarbonic anhydrase (CA) IX is a surface-expressed protein that is upregulated by the hypoxia inducible factor (HIF) and represents a prototypic tumor-associated antigen that is overexpressed on renal cell carcinoma (RCC). Therapeutic approaches targeting CAIX have focused on the development of CAIX inhibitors and specific immunotherapies including monoclonal antibodies (mAbs). However, current in vivo mouse models used to characterize the anti-tumor properties of fully human anti-CAIX mAbs have signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 61 publications
1
43
0
2
Order By: Relevance
“…Another important proof-of-principle experiment involved the injection of human NK cells into the blood of mice one day before their euthanasia. Our previous experience with this orthotopic ccRCC model in NSG mice showed that human NK cells last only for a few days in the mouse blood [31], and for this reason the injection of these NK cells was not performed until the end of the experiment. The results demonstrated the specific recruitment of human NK cells into the tumor of mice treated with anti-PD-L1 IgG1-secreting anti-CAIX CAR T cells.…”
Section: Figure 5: Exhaustion Markers On Tumor Infiltrating Lymphocytmentioning
confidence: 99%
“…Another important proof-of-principle experiment involved the injection of human NK cells into the blood of mice one day before their euthanasia. Our previous experience with this orthotopic ccRCC model in NSG mice showed that human NK cells last only for a few days in the mouse blood [31], and for this reason the injection of these NK cells was not performed until the end of the experiment. The results demonstrated the specific recruitment of human NK cells into the tumor of mice treated with anti-PD-L1 IgG1-secreting anti-CAIX CAR T cells.…”
Section: Figure 5: Exhaustion Markers On Tumor Infiltrating Lymphocytmentioning
confidence: 99%
“…These inventions cascaded into a series of immunodeficient mice and their variants (BRG, NOG, NRG) (Ali et al 2012; Grover et al 2017; Ishikawa et al 2005; Katano et al 2014; Koboziev et al 2015; Shultz et al 2005) being innovated which enabled in-depth analysis in research areas, such as human hematopoiesis (Rongvaux et al 2011; Yong et al 2016), innate and adaptive immunity (Brehm et al 2010; Pearson et al 2008), autoimmunity (Gunawan et al 2017; Viehmann Milam et al 2014), infectious disease (Keng et al 2015; Lüdtke et al 2015; Wege et al 2012), cancer biology (Chang et al 2015; Her et al 2017; Morton et al 2016), and GvHD (King et al 2008; Kirkiles-Smith et al 2009; Zhao et al 2015), in-turn, facilitating the development of therapeutic agents and novel vaccines. An overview of genotypic and physiological characteristics of each model is outlined in Tables 1 and 2.…”
Section: Evolving History Of Humanized Micementioning
confidence: 99%
“…Chang et al humanized an orthotopic renal cell carcinoma (RCC) model mouse with PBMCs to examine the effectiveness of an antibody targeting the carbonic anhydrase IX protein expressed in RCC showing that this antibody primed T cells and inhibited cancer growth (30). Finally, while examining a novel immunotherapy against melanoma, Hu et al generated HMs from CD34+ HSPCs engineered to express an HLA class I-restricted melanoma antigen (MART-1)-specific TCR gene (31).…”
Section: State Of the Art In Cancer Researchmentioning
confidence: 99%